Development and Characterization of PES/ EDA-Functionalized TiO2 Mixed Matrix Membrane for CO2 Removal from Natural Gas - El-tahir Mustafa, Sara Galal El-din (Universiti Teknologi PETRONAS, 2016)
The use of mixed matrix membranes is progressively growing in the field of gas separation applications. However poor adhesion between the polymer matrix and inorganic filler is a key challenge that consequences in a declined separation performance. Modification techniques of the inorganic fillers, such as amine-graftinghave been introduced in the synthesis of mixed matrix membrane in order to enhance the compatibility between the filler and the polymer matrix In this present work, mixed matrix membranes using polyethersulfone as the polymer phase and pristine TiO2 nanoparticles as well as ethylenediamine-grafted TiO2 nanoparticles as the inorganic filler at different loadings (5, 10 and 15% wt) were synthesized via dry phase inversion method. Membranes embedded with ethylenediamine-TiO2 exhibited and enhanced morphology and thermal stability as per revealed by field emission scanning electron microscopy and thermogravimetric analysis respectively as compared to membranes incorporated with pristine TiO2 particles.